An Action Research on The Effect of Using Real Modeled Object in Teaching Orthographic Drawing Concepts on Students’ Performance - Mohd Salehudin Marji; Aede Hatib Musta'amal; Chinedu Caleb Chidozie; Syafiq Che Hassan (Mathematics Education Study Program, 2023)
Computer-Aided Design (CAD) has become a common tool used by educational institutions in teaching engineering drawing. Although more practical, learning that relies too heavily on CAD can lead to a decrease in students' ability to visualize and interpret technical drawing objects. This study will examine the integration of CAD in technical drawing education with the use of real model objects in the orthographic drawing and its impact on students’s performance. The study employed a three-step data collection approach, including a pre-test, intervention, and post-test, as well as a questionnaire to determine students' perceptions of the learning process. The study participants were fifteen fourth-grade high school students from SMA Seri Aman, Kota Tinggi. The students had previously been taught orthographic drawing and had prior knowledge of the subject matter. Based on the regression testing results, a p-value of 0.00 <0.05 was obtained, indicating a significant relationship between real modeled object learning and students' learning performance. Additionally, based on the average scores, there was an improvement in each phase, with pre-test scores of 4.46 and post-test scores of 8.40, indicating that the use of real modeled objects significantly improved learning outcomes compared to conventional learning models in orthographic drawing materials.